Health technologies for falls prevention and detection in adult hospital in-patients: a scoping review protocol. (May 2019) - Alexander, Lyndsay; Swinton, Paul; Kirkpatrick, Pamela; Stephen, Audrey; Mitchelhill, Fiona; Simpson, Susan; Cooper, Kay
Abstract : Review objective/questions: The objective of this scoping review is to map the evidence relating to the reporting and evaluation of health technologies for the prevention and detection of falls in adult hospital in-patients. The following questions will guide this scoping review: What falls prevention and detection health technologies have been reported in the literature? What outcomes have been reported that measure falls prevention and detection health technologies in terms of clinical effectiveness, cost-effectiveness, acceptability and feasibility of use?